Permeability Characteristics of Coal after Supercritical CO2 Adsorption at Different Temperatures - Xueying Liu; Jin Yu; Di Wu; Xiaochun Xiao (Geofluids)
CO2 storage in coal seams has become one effective method to reduce CO2 emission and help exploit coalbed methane (CBM). The permeability is a key parameter for CBM extraction. In deep coal seams (>800 m), CO2 exists in the supercritical state. In the present work, permeability tests were performed on briquettes before and after supercritical CO2 (SC-CO2) adsorption at various temperatures to investigate the effects of SC-CO2 adsorption on the permeability. Experimental results show that SC-CO2 adsorption leads to volumetric expansion and permeability augment. The permeability enhancement decreases continuously at 35°C, while it initially increases and reduces at pressures exceeding 9 or 10 MPa at 45 or 55°C, respectively. Besides, the permeability enhancement ratio shows a linear increase with the expansion. The research provides a basis for further research on the enhanced coalbed methane (ECBM) recovery.